The digital divide Internet and e-mail use by the elderly. - Kiel, Joan M. (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
The elderly are the fastest growing population group. Along with their rise in numbers is their volume of use of health care services, in both number and intensity. Since many elderly live alone, can their independence be maintained such that health care costs can decrease? With the rise in technology utilization, specifically the Internet, can the elderly utilize the Internet for health care purposes? Survey methodologies conducted for this study showed that the elderly can learn to use computers and are looking for methods to stay connected and be informed. Further longitudinal research is needed to measure clinical outcomes.